Two-year Carcinogenicity Study in Rats with a Nonnucleoside Reverse Transcriptase Inhibitor. (April 2015) - Nambiar, Prashant R.; Morton, Daniel; Dochterman, Leland Wayne; Houle, Christopher; Thomford, Peter J.; Fate, Gwendolyn; Bailey, Steven A.; Finch, Gregory L.
Administration of lersivirine, a nonnucleotide reverse transcriptase inhibitor, daily by oral gavage to Sprague-Dawley rats for up to 2 yr was associated with decreased survival, decreased body weights, and an increase in neoplasms and related proliferative lesions in the liver, thyroid, kidney, and urinary bladder. Thyroid follicular adenoma and carcinoma, the associated thyroid follicular hypertrophy/hyperplasia, hepatocellular adenoma/adenocarcinoma, altered cell foci, and hepatocellular hypertrophy were consistent with lersivirine-related induction of hepatic microsomal enzymes. Renal tubular adenoma and renal tubular hyperplasia were attributed to the lersivirine-related exacerbation of chronic progressive nephropathy (CPN), while urinary bladder hyperplasia and transitional cell carcinoma in the renal pelvis and urinary bladder were attributed to urinary calculi. Renal tubular neoplasms associated with increased incidence and severity of CPN, neoplasms of transitional epithelium attributed to crystalluria, and thyroid follicular and hepatocellular neoplasms related to hepatic enzyme induction have low relevance for human risk assessment.